Donor-Acceptor Dyads and Triads Employing Core-Substituted Naphthalene Diimides: A Synthetic and Spectro (Electrochemical) Study - Samuel Quinn; E. Stephen Davies; Nicholas Pearce; Callum Rosenberg; Constance R. Pfeiffer; Georgia R. F. Orton; Neil R. Champness (Molecules, 2022)
Donor-acceptor dyads and triads comprising core-substituted naphthalene diimide (NDI) chromophores and either phenothiazine or phenoxazine donors are described. Synthesis combined with electrochemical and spectroelectrochemical investigations facilitates characterisation of the various redox states of these molecules, confirming the ability to combine arrays of electron donating and accepting moieties into single species that retain the redox properties of these individual moieties.